Role of Epigenetic Regulatory Mechanisms in the Mechanism of Essential Hypertension - Guang-Wei, Zhong; Yan-Hong, Luo; Wei, Li; Chang-Gao, Zhong; Cheng, Zhang (Current Hypertension Reviews, 2010)
Hypertension is among the common and leading causes of morbidity and mortality throughout the globe. The biological process of hypertension involves multiple physiological pathways, each of which may be affected by multiple gene products. But the mechanisms under this difference are still not full understood. In recent years, some evidence has been found supporting the involvement of epigenetic mechanisms in many cardiovascular diseases and others. We hypothesised that epigenetic mechanisms have been also involved in essential hypertension possibly by suppression of and changing the relational genes with essential hypertension.
Keywords: insulator pro-teins